Pigovian Transport Pricing in Practice - Hintermann, Beat; Schoeman, Beaumont; Molloy, Joseph; Götschi, Thomas; Castro, Alberto; Tchervenkov, Christopher; Tomic, Uros; Axhausen, Kay W (Review of Economic Studies, 2026)
We implement Pigovian transport pricing in a field experiment in urban agglomerations of Switzerland over the course of 8 weeks. Our pricing considers the external costs from climate damages, health outcomes from pollution, accidents and physical activity, and congestion. It varies across time, space, and mode of transport and is deducted from a budget provided to GPS-tracked participants. The treatment significantly reduces the external costs of transport during the course of the experiment. The main underlying mechanism is a shift away from driving towards other modes, such as public transport, walking, and cycling. Providing information about the external costs of transport alone is insufficient to change the transport behaviour for the sample majority. A time-invariant tax on CO2 and health-related externalities would capture most of the welfare gains associated with the first-best policy.